Influence of MHD and Wall Properties on the Peristaltic Transport of a Williamson Fluid with Variable Viscosity Through Porous Medium - Al-Khafajy, Dheia G. Salih (Iraqi Journal of Science, 2022)
This paper concerns the peristaltic flow of a Williamson fluid with variable viscosity model through porous medium under combined effects of MHD and wall properties. The assumptions of Reynolds number and long wavelength is investigated. The flow is investigated in a wave frame of reference moving with velocity of the wave. The perturbation series in terms of the Weissenberg number (We <1) was used to obtain explicit forms for velocity field and stream function. The effects of thermal conductivity, Grashof number, Darcy number, magnet, rigidity, stiffness of the wall and viscous damping force parameters on velocity and stream function have been studied.